Estrogenic activity of the hydroalcoholic extract of the fruit of aguaje mauritia flexuosa l in ovariectomized rats - admin, admin (2018)
Objectives. To determine the estrogenic activity of hydroalcoholic extract of the fruit of aguaje (Mauritia flexuosa L) in ovariectomized rats. Materials and methods. 54 Sprague-Dawley rats from 2 1/2 to 3 months of age were grouped randomly into six groups: intact females + saline, ovariectomized + saline, hydroalcoholic extract of three different doses aguaje, ovariectomized + ethinylestradiol. After ovariectomy treatment was started by intragastric for 5 weeks. At 2 weeks of treatment a vaginal smear was made for 7 days to determine the cell maturation. At the end of the treatment was performed euthanasia to study the bone tissue of the proximal metaphysis of the tibia and the uterus was dissected for weighing. Results. The group that received doses of 500 mg/kg had more rats that had vaginal cell maturation in contrast to the lower dose. In the study of bone was not significant estrogenic activity in trabecular bone but it was a significant increase in osteoblasts in the groups treated with the hydroalcoholic extract of aguaje at doses of 100 mg/kg. Uterine weight in the groups treated with the extract and saline were similar ovariectomized. Conclusions. The hydroalcoholic extract of the fruit of aguaje presented in ovariectomized rats estrogen activity in cells vaginal dose of 100mg/kg produced a significant increase in the number of osteoblasts, and no evidence of estrogenic activity in uterine weight with any of the hydroalcoholic extract dose aguaje.